The effects of breastfeeding duration on children’s behavior problems at around 3 years of age - Gao, Lu; Yang, Jianhui; Strodl, Esben; Wu, Chuanan; Yin, Xiaona; Wen, Guomin; Sun, Dengli; Xian, Danxia; Chen, Weiqing (Frontiers in Nutrition, 2025)
BackgroundAlthough breastfeeding has been demonstrated to benefit children’s health in the initial stages, the lasting effects on behavioral development throughout childhood remain unclear. This study explored the associations between exclusive and overall breastfeeding duration and behavioral problems in Chinese children, aiming to establish evidence-based recommendations for their prevention and management.MethodsA cross-sectional study involving 17,867 3-year-old children in Longhua District, Shenzhen, China, used questionnaires to collect data on socio-economic status, breastfeeding patterns, and behavioral problems. Breastfeeding durations were analyzed as continuous and categorical variables. Logistic regression, linear regression, and spline plots were used to assess the relationships.ResultsAmong 17,867 children, 14.3% had behavioral problems. Exclusive breastfeeding for the first 6 months was significantly associated with lower psychosomatic problem scores. An L-shaped relationship was observed between the duration of exclusive breastfeeding and behavioral problems. Breastfeeding for ≥13 months, compared with ≤6 months, was associated with a lower risk of behavioral problems, particularly impulsive-hyperactivity, and lower scores for learning and psychosomatic issues. Additionally, a linear relationship was observed between total breastfeeding duration and behavioral problems.ConclusionAdequate exclusive breastfeeding and extended breastfeeding could reduce behavioral problems in Chinese children, but the causal directionality of observed associations remains undetermined due to cross-sectional data. Given the alignment with current breastfeeding guidelines, interventions to extend breastfeeding duration may help mitigate childhood behavioral problems. Further cohort studies are needed to confirm causality and understand long-term impacts.